2010
DOI: 10.1590/s1517-83822010000400027
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinus officinalis essential oil: antiproliferative, antioxidant and antibacterial activities

Abstract: The aim of this work was to investigate and compare the antiproliferative, antioxidant and antibacterial activities of Rosmarinus officinalis essential oil, native to Pakistan. The essential oil content from the leaves of R. officinalis was 0.93 g 100g -1 . The GC and GC-MS analysis revealed that the major components determined in R. officinalis essential oil were 1,8-cineol (38.5%), camphor (17.1%), -pinene (12.3%), limonene (6.23%), camphene (6.00%) and linalool (5.70%). The antiproliferative activity was te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
119
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(133 citation statements)
references
References 20 publications
6
119
0
8
Order By: Relevance
“…On general, there is no limitation on using the rosemary essential oil or their extract in meat products (Jordan Standards and Metrology Drganization, 2016). Rosemary oleoresin, extract, and their essential oils were reported as a potential antioxidant used widely in the food industry (Yu et al, 2002;Balentine et al, 2006;Hussain et al, 2010). On addition, it had been reported that rosemary extract (RE) was effective delaying lipid oxidation in meat (Georgantelis et al, 2007;Keokamnerd et al, 2008;Kahraman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…On general, there is no limitation on using the rosemary essential oil or their extract in meat products (Jordan Standards and Metrology Drganization, 2016). Rosemary oleoresin, extract, and their essential oils were reported as a potential antioxidant used widely in the food industry (Yu et al, 2002;Balentine et al, 2006;Hussain et al, 2010). On addition, it had been reported that rosemary extract (RE) was effective delaying lipid oxidation in meat (Georgantelis et al, 2007;Keokamnerd et al, 2008;Kahraman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Oils from both of these plants are known to contain ÎČ-caryophyllene oxide, which has been noted for signal cascade inactivation resulting in down-regulation of proliferation and angiogenesis in some cancer cell lines (Park et al, 2011;Kim et al, 2014). Oils from R. officinalis also have been reported to have high inhibitory values against a variety of cell lines (Hussain et al, 2010;Wang et al, 2012).…”
Section: Discussion Ic 50 and CC 50mentioning
confidence: 99%
“…Estudo realizado por Hussain et al, (2010) o Ăłleo essencial de alecrim possui boa atividade antimicrobiana sendo comparado ao controle ciprofloxacino. A atividade antimicrobiana do Ăłleo essencial pode ser atribuĂ­da aos compostos α-pineno, cĂąnfora, verbenona e borneol, sendo este o mais potente (SANTOYO et al, 2005 et al, (2005), extratos produzidos a partir de folhas desta planta demonstraram tal atividade contra S. mutans presentes na cavidade oral de humanos.…”
Section: Discussionunclassified